That stamps him - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
We know, from your comments, that the articles in Spore are extremely well read. But a letter sent in by Abayneh Mekonnen, from North Shoa, Ethiopia, wins the prize for attention to detail. He reads even the texts on the stamps in Mailbox and...